Subordinated debt, market discipline, and bank risk - Yehning Chen; Iftekhar Hasan (Bank of Finland, 2011)
This paper demonstrates that subordinated debt ( subdebt thereafter) regulation can be an effective mechanism for disciplining banks. Under our proposal, investors buy the subdebt of a bank only if they receive favourable information about the bank, and the bank is subject to a regulatory examination if it fails to issue subdebt. By forcing banks to be examined when they are likely weak, subdebt regulation not only reduces the chance that managers of distressed banks can take value-destroying actions to benefit themselves, but may also encourage banks to lower asset risk. It shows that subdebt regulation and bank capital requirements can be complements for alleviating the banks moral hazard problems. It also suggests that to make subdebt regulation effective, regulators may need impose ceilings on the interest rates of subdebt, prohibit collusion between banks and subdebt investors, and require the subdebt to convert into the issuing bank s equity when the government takes over or provides open assistance to the bank.
URN:NBN:fi:bof-20140807613
Keywords: 330